Association of concomitant headache with hypoperfusion in ischemic stroke: A multimodal CT‐based study. Issue 12 (30th September 2022) - Ge, Yi; Dong, Wanli; Lu, Haifeng; Zhang, Ximeng; Huang, Shicun; Yang, Yi; Ni, Jianqiang
Abstract: Previous investigations indicate that vessel wall elasticity may contribute to the occurrence of an ischemic stroke‐associated headache. In this prospective study, the association between radiologic parameters of intracranial hemodynamic changes and concomitant headaches during the early phase of ischemic stroke was examined. Consecutive patients with acute ischemic stroke (AIS) from the First Affiliated Hospital of Soochow University were recruited and divided into two groups according to their questionnaire results and the International Classification of Headache Disorder 3 criteria. Baseline data, including stroke sub‐types and neurological function, at admission and discharge were collected. Non‐contrast computed tomography (CT), CT angiography, and CT perfusion were performed to assess intracranial hemodynamic changes. Multiple adjusted logistic models were used and possible confounding factors were included in sequential models. A total of 190 patients with AIS (93 headaches and 97 non‐headache) were recruited. There were significant differences between the two groups in gender, hypertension, Alberta stroke program early CT score, relative cerebral blood flow (rCBF), and relative cerebral blood volume (rCBV). Furthermore, rCBV (adjusted odds ratio [OR] 0.160; 95% confidence interval [CI], 0.055–0.461; p < 0.001) and rCBF (adjusted OR, 0.309; 95% CI, 0.113–0.844; p < 0.05) were significantly associated with concomitant headache during the early phase of AIS in fully adjusted models. After adjusting for sociodemographic characteristics and other confounding factors, p values for the ORs were robust and intensified. Patients with lower rCBV and rCBF tended to experience the concomitant headache during the early phase of AIS. Regional hypoperfusion and microcirculation might play an important role in this separate clinical entity.